AN ONTOLOGY DESIGN FOR TURKISH ADMINISTRATIVE UNIT GAZETTEER - Kara, Abdullah; Cagdas, Volkan (YILDIZ TECHNICAL UNIV, 2014)
Digital gazetteers are seen as the basic building blocks of the Web-based mapping services and spatial search engines. The most recent local and global gazetteer development initiatives have focused on representing gazetteers as Linked Data, by using the Resource Description Framework (RDF). In the present study, an ontology model, namely Turkish Administrative Units Ontology is developed for publication of administrative unit gazetteer as Linked Data. The developed ontology, represented by Web Ontology Language (OWL), specifies Turkish administrative units, their locations and properties, as well as spatial relationships (i.e. mereological and topological relationships) between these units. The Linked Data representation of administrative units enables integration of all RDF datasets (e.g. population, taxation, public services, statistics) prepared by different public organizations for the same administrative units. This approach facilitates accessing all administrative unit related information via Web, without making any additional search.
Keywords: Linked data; ontology; semantic web; gazetteer; geographic information system; Engineering